2019
DOI: 10.3390/brainsci9120380
|View full text |Cite
|
Sign up to set email alerts
|

Typical and Aberrant Functional Brain Flexibility: Lifespan Development and Aberrant Organization in Traumatic Brain Injury and Dyslexia

Abstract: Intrinsic functional connectivity networks derived from different neuroimaging methods and connectivity estimators have revealed robust developmental trends linked to behavioural and cognitive maturation. The present study employed a dynamic functional connectivity approach to determine dominant intrinsic coupling modes in resting-state neuromagnetic data from 178 healthy participants aged 8–60 years. Results revealed significant developmental trends in three types of dominant intra- and inter-hemispheric neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Additionally, we observed a significantly lower global FI in SSDs compared to HC only in amplitude driven DoCM. In a recent lifespan study with healthy controls, we found aberrant FI for two groups, a dyslexic group and a mild traumatic brain injury (Dimitriadis et al, 2019). FI can be seen as a global index of the normal multiplexity behavior of nested oscillations.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, we observed a significantly lower global FI in SSDs compared to HC only in amplitude driven DoCM. In a recent lifespan study with healthy controls, we found aberrant FI for two groups, a dyslexic group and a mild traumatic brain injury (Dimitriadis et al, 2019). FI can be seen as a global index of the normal multiplexity behavior of nested oscillations.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, we observed a significant lower global FI in SSDs compared to HC only in amplitude driven DoCM. In a recent lifespan study with healthy controls, we found aberrant FI for two groups, a dyslexic group and a mild traumatic brain injury (Dimitriadis et al, 2019). FI can be seen as a global index of the normal multiplexity behaviour of nested oscillations.…”
Section: Discussionmentioning
confidence: 80%
“…In our previous study, we reported for the very first time that a long-term intervention with HP-EH-EVOO or MP-EVOO was associated with significant improvement in cognitive function compared to the MeDi group [7]. We adopted our DoCM model, which incorporates into a dFCG both the dominant coupling mode and its functional strength between every pair of EEG sensors and across experimental time [43,[50][51][52][53][54][55][56][57][58]. We detected a significant higher postintervention reduction of NI (ΔΝΙ Total and α ) for the HP-EH-EVOO compared to the MP-EVOO and MeDi groups.…”
Section: Discussionmentioning
confidence: 99%
“…This section will briefly describe our dominant intrinsic coupling model (DoCM) demonstrated in the whole repertoire of functional neuroimaging modalities [41,43,[49][50][51][52][53][54][55][56][57][58].…”
Section: The Integrated Dynamic Functional Connectivity Graph (Idfcg) Based On Iplvmentioning
confidence: 99%
See 1 more Smart Citation